Renewal of Organizational Competencies: The Case of Polish ex-Socialist Companies in the Economic Transition Period - Kaminska-Labbé, Renata; Thomas, Catherine; McKelvey, Bill (Journal of Public Governance, 2018)
The abolition of centralized economy systems in Eastern and Central European countries is an unprecedented situation in which firms, markets, social and institutional systems undergo a process of complete reconstruction. Changes in their economic environment make Polish post-socialist firms to invent strategies and organizational designs adapted to the post-rupture context of economic transition. On the basis of a long-term case study of three ex-socialist Polish firms which have survived the first decade of the economic transition, we analyze how these firms adapt to the new social-economic environment and more precisely how they build new competencies. Two additional questions are also addressed: first, the role of history and path dependence in the process of building new competencies and second, the co-evolution of competence-building with the environment. The analysis of data based on the methodology proposed by Huberman and Miles (1991) focuses on: the role of actors, the processes of competencebuilding and competence-building driving forces. The main conclusion drawn is that the regulation capacity is a key component of dynamic capabilities and a mediating variable of building new competencies. Therefore, in the post-rupture deconstruction context strategic renewal necessitates the emergence of a new regulation process based on deeply modified signification, domination and legitimization structures (Giddens, 1987). We suggest that this result could be extended to other post-rupture contexts marked by rapid environmental change.